Perancangan Interior Library-CafÃ© â€œStory Lineâ€ di Surabaya - Vianny, Grace; Indrani, Hedy Constancia; Kattu, Grace Setiati (Intra, 2019)
Library is one of the facilities to support educational and information needs. The existence of libraries is now becoming less attractive to the public, especially teenagers, apart from educational needs, this is because there are many emerging modern places for recreation that adjusts visitor’s desire especially in Surabaya. This situation causes people’s interest on reading becomes lower at Surabaya. The idea is to renew the rigid and formal library concept into a relaxing and fun library by combining library with café which is a favorite place for teenagers nowadays. The library-cafe that will be designed has the concept Creative Comfy Zone to accommodate literacy activities in it in a comfortable ambience. Memphis Style is a complement to this design to become different from existing libraries. This idea is expected to help increasing teenagers' reading interest.